Microbiological Study of Escherichia Coli Contamination in Dug Wells in Demak District, Central Java - Santi, Narulita; Fanny, Celsy Miftaqul Tiara; Pangestuti, Dina Rahayuning; Putranto, Thomas Triadi; Putri, Maya Aiko Salsabila (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
Demak Regency is a peri-urban area in Java experiencing an increasing demand for clean water due to population growth and development. Groundwater is the primary source to meet this demand, although its quality is often threatened by pollution from household waste and unprotected septic tanks. This study aims to evaluate groundwater quality in Demak District with the Escherichia coli presence parameter in unconfined aquifers using a GIS-based spatial approach and IDW interpolation method. The geology of the study area includes sandstone, carbonate mudstone, and alluvium lithologies, with most regions having flat slopes. The hydrogeological potential of the study area shows diverse aquifer productivity, with groundwater levels ranging from 0.3–41 meters. The results of the groundwater quality analysis in the study area showed that 47% of the samples exceeded the safe limit for Escherichia coli by Ministry of Health Number 2 Year 2023. The shallow depth of the groundwater table and poor well construction allow the infiltration of contaminants from the land surface into the groundwater, especially from polluting sources around the well. This study provides an essential overview of groundwater quality in the Demak District, which can support sustainable groundwater management and improved sanitation to improve public health.